Corporate Communications and Public Relations: Technological Transformation and Digitalization Towards Society 5.0 - Constantin, Natasha; Nelwin, Raynaldi; Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
The insurance sector is undergoing a substantial shift in the swiftly changing environment of society 4.0, entering society 5.0 marked by digitization, mobile technologies, and artificial intelligence (AI). The formerly deemed conservative sector increasingly embraces innovative technology to improve operational efficiency and transform consumer interaction. This paper examines the influence of mobile and AI technologies on corporate communication and public relations, explicitly analyzing their effects on the insurance industry via the perspective of technological determinism. The objective is to examine how new technologies transform consumer interactions, trust dynamics, and organizational tactics while addressing ethical issues such as AI transparency and data protection. This study, rooted in technological determinism, highlights technology's independent and socially influenced effects on organizational behaviors. It uses a qualitative approach, phenomenological method, and semi-structured interviews with industry experts to investigate lived experiences and insights. The findings indicate that mobile platforms improve consumer interaction through immediacy and accessibility, while AI enhances operations through predictive analytics and automation. Nonetheless, issues about diversity and ethical responsibility persist as significant concerns. The research suggests that mobile and AI technologies serve as transformational agents, necessitating enterprises to reconcile technical innovation with ethical accountability. By implementing inclusive, transparent, and proactive communication strategies, insurance businesses may use these technologies to cultivate trust, enhance stakeholder relationships, and adeptly negotiate the intricacies of Society 4.0. This study offers a framework for incorporating developing technology into corporate communication and public relations by social norms and expectations.